The evolution of a strike-slip fault network in the Guchengxu High, Tarim Basin (NW China). (June 2022) - Qiu, Huabiao; Deng, Shang; Zhang, Jibiao; Lin, Huixi; Huang, Cheng; Han, Jun; Lin, Wei; Zhu, Xin
Abstract: Convergent plate margins could have an immediate impact on intraplate deformation in the adjacent sedimentary basin. In the Tarim Basin, a strike-slip fault network in the Guchengxu High is adjacent to the Tethys (northern Tibetan Plateau). This paper uses high-quality 3-D seismic data to unravel the geometry and kinematics of the strike-slip fault network and the genetic relationship with the Tethys tectonics. Within the fault network, the left-lateral NNE- and ENE-oriented strike-slip faults are a result of sequential evolution rather than conjugate faults. The sub-vertical ENE-oriented strike-slip faults are widely spaced with stepping-segmented geometry in the west, whereas they are relatively clustered with larger vertical throws close to the Cherchen fault. They were interpreted as a series of the Cherchen fault-related structures due to oblique blocking of the Tazhong Uplift and block deflection. It responded to the Late Ordovician Altyn Tagh/Tarim collisional orogeny and the Cherchen fault. The NNE-oriented strike-slip faults are characterized by underlying sub-vertical faults and two layers of overlying normal faults. These NNE-oriented strike-slip faults have large transversal compressional components, commonly presenting reverse drags on both sides of the underlying sub-vertical faults. These NNE-oriented faults initiated on pre-existing discontinuities (extensional joints) and offset the ENE-oriented ones when NNW-oriented stress was transmitted to plate interiors during this Late Ordovician orogeny. Afterward, two layers of overlying normal faults formed due to dragging of the covers during the Middle Silurian–Early Carboniferous reactivation and the Late Carboniferous–Early Permian inversion, in response to subduction of the Kunlun Ocean and opening of the Paleo-Tethys Ocean, respectively. The strike-slip fault network in plate interiors evolved as immediate responses to the Tethys tectonics at plate boundaries. Highlights: The 3-D seismic data detailedly characterize the strike-slip fault network in the Guchengxu High. The strike-slip fault network is a result of sequential evolution rather than a series of conjugate faults. The strike-slip fault network in the Guchengxu High evolved in response to the Tethys tectonics at plate boundaries.